The structure of civil proceedings: convergence through the main hearing model? - Nylund, Anna (Civil Procedure Review, 2018)
Traditionally, European civil procedure systems have displayed a range of structures. Currently, systems are converging around the main hearing model, which international soft law initiatives on civil procedure also endorse. This text discusses the main content and principles of the main hearing model and its application in English, Finnish, German and Norwegian law. The influence of the underlying structure of civil proceedings and the legal culture, in particular the role of the judge is explored through a comparison of the four countries. Finally, the qualities of the main hearing model are discussed, as is the way to successful implementation of the main hearing model as a tool to achieve efficient proceedings leading to quality outcomes.